Digital twin and contact analysis of ultra-long distance coiled tubing operation structures [version 2; peer review: 1 approved, 2 approved with reservations] - Wenlan Wei; Jiarui Cheng; Hao Qu; Maliang Wang; Wenyuan Wang (Digital Twin)
Background Coiled tubing operation is a high-quality operation method that considers both cost and efficiency in current oil and gas well operations. There is a significant difference between the calculation and prediction before operation and the actual operation. The reason is that the complex wellbore trajectory makes it difficult to evaluate the contact state between coiled tubing and wellbore, resulting in a significant error in the pipe string mechanics calculation and analysis. Methods In this study, a digital twin-based method for continuous tubing wear modelling is proposed. Firstly, the digital twin unit of continuous tubing-wellbore is constructed to achieve the fusion modelling of three types of information, namely structure, physical field and material, of the micro-element well section. On this basis, a feedback-corrected contact algorithm is introduced to dynamically identify and correct the contact state of continuous tubing under different downhole running trajectories. By constructing a spatial and temporal two-dimensional digital twin of the continuous tubing operation process, the accurate positioning and historical state tracing of the tubing entity in the complex downhole environment are realised. Results The research results show that the digital twin coiled tubing and contact algorithm can effectively predict the contact state of coiled tubing operations; the verification model shows that the contact algorithm can accurately analyze the contact state of different well trajectories. Conclusions The digital twin of the coiled tubing operation structure and its contact algorithm can effectively solve the problem of deterministic friction state in the process of mechanical calculation of the tubing string, which has important guiding significance and engineering value for the mechanical calculation and operation safety analysis of coiled tubing operation.